Publicity and the Clustering of IPO Underpricing - Melanie Cao; Shouyong Shi (Queen's University, Department of Economics, 1999)
We explain why underpricing in IPOs can be large in magnitude and clustered, using a signalling model where firms have private information about their qualities (high or low). A novel feature is that a firm, if perceived by the market as high quality, benefits from the industry's publicity which is an increasing function of the amount of IPO underpricing by all high-quality firms in the industry. Despite the potential free-rider problem created by the industry's publicity, we show that a high-quality firm chooses to underprice its own IPO as the best response to other high-quality firms' underpricing. Thus, IPO underpricing is clustered.
Keywords: G30; D82; 330; Initial public offering; Signalling; Externality; Multiple equilibria